When someone you love suffers from posttraumatic stress : what to expect and what you can do - Zayfert, Claudia; DeViva, Jason C. (The Guilford Press, 2011)
"Trauma survivors frequently struggle with unwanted memories, intense emotions, and problems with everyday functioning. Effective help is out there, but the needs of family members--confused and scared about what has happened to the person they love--are often overlooked. Will the person with posttraumatic stress ever get better? How can spouses and other loved ones promote healing? Where can family members turn when they feel like they just can't cope? From experienced trauma specialists Drs. Claudia Zayfert and Jason C. DeViva, this highly practical guide is packed with information, support, vivid stories, and specific advice. Readers learn to navigate the rough spots day by day and help their loved one find a brighter tomorrow"